Mycophenolate mofetil therapy in the management of inflammatory bowel disease — A retrospective case series and review. (1st August 2014) - Smith, Matthew R.; Cooper, Sheldon C.
Abstract: Background and aims: The role of mycophenolate mofetil (MMF) as an immunomodulatory drug in managing inflammatory bowel disease (IBD) is yet to be fully defined. We reviewed our experience of MMF in treating patients with IBD. Methods: Retrospective analysis was performed on all patients treated with MMF for inflammatory bowel disease between 2003 and 2011. Remission was assessed by reviewing clinical, endoscopic and laboratory indices. Results: We identified 36 patients, 23 male (64%), median age 46 years (range 19–75). Nineteen patients had Crohn's disease, 16 with ulcerative colitis (UC), and one with indeterminate colitis. 33 patients (92%) had previously received azathioprine; 32 of whom discontinued this due to side-effects. 26 patients (72%) were concurrently taking oral corticosteroids. Median length of MMF treatment observed was 21.5 months (IQR 9.7–31.6). At 8 weeks, 29 patients (81%) had either achieved or maintained remission. After 6 months, 19 of 33 patients (58%) were in sustained steroid-free remission. At the end of the observation period, 29 patients (81%) remained on MMF. 13 patients (36% of original treatment group; UC/IBDU 8, Crohn's 5) maintained steroid free remission. Median time in remission was 21.4 months (IQR 11.0–30.0). Drug side-effects were experienced by 7 patients (19%), managed by dose reduction in 5 patients, with discontinuation in 2 (6%). Conclusions: Mycophenolate mofetil may represent a promising treatment for inducing and maintaining remission in IBD patients intolerant of thiopurines. It may be of more value and relevance in ulcerative colitis, since less alternative proven therapies are available.